Detection of Polycystic Ovarian Syndrome: A Literature Survey - Saravanan, A.; Sathiamoorthy, S. (Asian Journal of Engineering and Applied Technology, 2018)
Polycystic ovarian syndrome is an endocrine issue attacking ladies at the age of reproduction. This indication has primarily found in ladies whose age is in the middle of 25 and 35. It is essential to diagnose and recognize diverse types of ovulatory failure that can add to infertility. There are numerous clarifications for ovulation failure. Without distinguishing the correct locality of the follicle, the risk seriousness of the patient can’t reveal. In line with this, many of the researchers focusing their research interest in PCOS. In this paper, literature review on polycystic ovarian syndrome using machine learning and image processing has exhibited.